Transit and non‐transit 3D EPID dosimetry versus detector arrays for patient specific QA - Olaciregui‐Ruiz, Igor; Vivas‐Maiques, Begoña; Kaas, Jochem; Perik, Thijs; Wittkamper, Frits; Mijnheer, Ben; Mans, Anton (Journal of applied clinical medical physics, 2019)
Purpose Despite their availability and simplicity of use, Electronic Portal Imaging Devices (EPIDs) have not yet replaced detector arrays for patient specific QA in 3D. The purpose of this study is to perform a large scale dosimetric evaluation of transit and non‐transit EPID dosimetry against absolute dose measurements in 3D. Methods After evaluating basic dosimetric characteristics of the EPID and two detector arrays (Octavius 1500 and Octavius 1000SRS), 3D dose distributions for 68 VMAT arcs, and 10 IMRT plans were reconstructed within the same phantom geometry using transit EPID dosimetry, non‐transit EPID dosimetry, and the Octavius 4D system. The reconstructed 3D dose distributions were directly compared by γ‐analysis (2L2 = 2% local/2 mm and 3G2 = 3% global/2 mm, 50% isodose) and by the percentage difference in median dose to the high dose volume (%∆HDVD50). Results Regarding dose rate dependency, dose linearity, and field size dependence, the agreement between EPID dosimetry and the two detector arrays was found to be within 1.0%. In the 2L2 γ‐comparison with Octavius 4D dose distributions, the average γ‐pass rate value was 92.2 ± 5.2%(1SD) and 94.1 ± 4.3%(1SD) for transit and non‐transit EPID dosimetry, respectively. 3G2 γ‐pass rate values were higher than 95% in 150/156 cases. %∆HDVD50 values were within 2% in 134/156 cases and within 3% in 155/156 cases. With regard to the clinical classification of alerts, 97.5% of the treatments were equally classified by EPID dosimetry and Octavius 4D. Conclusion Transit and non‐transit EPID dosimetry are equivalent in dosimetric terms to conventional detector arrays for patient specific QA. Non‐transit 3D EPID dosimetry can be readily used for pre‐treatment patient specific QA of IMRT and VMAT, eliminating the need of phantom positioning.